2019
DOI: 10.21315/tlsr2019.30.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Partial Characterisation of Thermophilic Cellulolytic Bacteria from North Malaysian Tropical Mangrove Soil

Abstract: This study reports the biodiversity of thermophilic cellulolytic bacterial strains that present in the north Malaysian mangrove ecosystem. Soil samples were collected at the four most northern state of Malaysia (Perak, Pulau Pinang, Kedah and Perlis). The samples obtained were first enriched in nutrient broth at 45°C and 55°C prior culturing in the carboxymethylcellulose (CMC) agar medium. Repeated streaking was performed on the CMC agar to obtain a pure culture of each isolate prior subjecting it to hydrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 30 publications
2
31
0
3
Order By: Relevance
“…Bacteria are considered as potent and functional enzyme producer due to their high growth rate, availability of multi-enzyme complexes and stability at the harsh condition (Ladeira et al, 2015). Several studies have demonstrated diverse useful potential of bacteria isolated from mangrove ecosystems (Behera et al, 2014a;Kunasundari et al, 2017;Naresh et al, 2019;Soares Júnior et al, 2013). Our findings confirm that mangrove rhizospheres are a source of diverse bacterial communities that have been shown to produce secondary metabolites.…”
Section: Discussionsupporting
confidence: 80%
“…Bacteria are considered as potent and functional enzyme producer due to their high growth rate, availability of multi-enzyme complexes and stability at the harsh condition (Ladeira et al, 2015). Several studies have demonstrated diverse useful potential of bacteria isolated from mangrove ecosystems (Behera et al, 2014a;Kunasundari et al, 2017;Naresh et al, 2019;Soares Júnior et al, 2013). Our findings confirm that mangrove rhizospheres are a source of diverse bacterial communities that have been shown to produce secondary metabolites.…”
Section: Discussionsupporting
confidence: 80%
“…This enzyme is reportedly produced by both bacteria (e.g., Bacillus spp.) [52] and fungi (Fusarium spp. and Aureobasidium spp.)…”
Section: Potential Soil Microbial Ecological Functionsmentioning
confidence: 99%
“…Especially, the genus Bacillus belonging to the phylum Firmicutes was dominant genus. In addition, several thermostable cellulases were also isolated (Kalaiselvi et al 2013;Naresh et al 2019). Meanwhile, based on metagenomic approaches, bacteria belonging to three phyla, Proteobacteria, Firmicutes and Actinobacteria were detected as cellulose-degrading bacteria, and a novel β-glucosidase and a endoglucanase were cloned and characterized (Li et al 2012;Mai et al 2014;Thompson et al 2013;Ottoni et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…and one Paenibacillus sp. from four mangrove areas in northern part of Malaysia (Perak, Pulau Pinang, Kedah and Perlis) (Naresh et al 2019). In addition, a novel actinobacterium, Streptomyces monashensis, which can produce antioxidants, exhibited cellulose degradation (Law et al 2019).…”
Section: Degradation Mechanisms Of Cellulose Hemicellulose and Pectinmentioning
confidence: 99%